2018
DOI: 10.1371/journal.pone.0190775
|View full text |Cite
|
Sign up to set email alerts
|

First report of occult hepatitis B infection among ART naïve HIV seropositive individuals in Maputo, Mozambique

Abstract: BackgroundThe prevalence of hepatitis B virus (HBV) infection and human immunodeficiency virus (HIV) infection in Mozambique is one of the highest in the world, though in spite of this the prevalence of occult hepatitis B infection (OBI) is unknown.ObjectivesThis study was conducted with the aim to investigate the prevalence of OBI and frequency of isolated hepatitis B core antibody (anti-HBc alone) among antiretroviral (ART) naïve HIV-positive patients in Mozambique.MethodsA cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
2
16
3
Order By: Relevance
“…The findings of this study with that regard therefore remain valid. This HBsAg prevalence was similar to the 6% found by Harania in 2008 at AKUHN, one of the sites in this present study [13] but lower than what is described in other parts of SSA of 8.7 to 11.7% [9,10,[14][15][16]. This is in keeping with Kenya being one of the few countries with intermediate HBV endemicity in a region that is generally hyper-endemic for HBV [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study with that regard therefore remain valid. This HBsAg prevalence was similar to the 6% found by Harania in 2008 at AKUHN, one of the sites in this present study [13] but lower than what is described in other parts of SSA of 8.7 to 11.7% [9,10,[14][15][16]. This is in keeping with Kenya being one of the few countries with intermediate HBV endemicity in a region that is generally hyper-endemic for HBV [17].…”
Section: Discussionsupporting
confidence: 90%
“…The effect of OBI on liver fibrosis and cirrhosis is still unknown. Bell et al in South Africa and Carimo et al in Mozambique found higher APRI scores in OBI patients compared to HBV negative patients, [9,15] a finding not demonstrated by Ryan et al in Botswana [14]. Our study, which was limited by low number of patients who had these scores available, showed numerically higher APRI scores in overt and occult HBV infection compared to HBV negative, although this did not reach significance (P 0.054).…”
Section: Plos Onecontrasting
confidence: 72%
“…Recently, a study conducted in HIV patients naive to antiretroviral therapy in Mozambique reported an OBI prevalence of 8.2%. (12) The difference in the prevalence reported in our study and that of Carimo et al may be attributed to (i) differences in the study population group (HIV patients are at higher risk of OBI due to immunodeficiency), (ii) the inclusion criteria utilized by Carimo et al that may lead to over or underestimation of OBI cases. With this criteria, only patients with anti-HBc alone were submitted to PCR assay and a portion of HBsAg gene was amplified and (iii) the pooling method used to determine HBV DNA might explain the low frequency of OBI observed in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…(9,10) Recently, Viegas et al, (11) reported a higher prevalence of 12.2% in 18-24 year-olds in the capital of Maputo. Carimo et al, (12) reported an 8.3% frequency of OBI among patients who were anti-HBc positive. The aim of this study was to characterize serological markers (anti-HBc, anti-HBs and HBeAg), viral genotypes, and mutations associated with OBI among blood donors.…”
mentioning
confidence: 97%
“…Specimens collected from a total of 305 individuals were examined. Overall, 67.8% of patients were women, with a median age of 26 years (interquartile range, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. A total of 41 patients presented with at least one viral infection (13.4%), coinfections were only found in one person.…”
Section: Resultsmentioning
confidence: 99%